PENENTUAN NILAI PREMI ASURANSI PERTANIAN PADA KOMODITAS KOPI BERBASIS HARGA INTERNASIONAL MENGGUNAKAN MODEL MEAN REVERSION DENGAN LOMPATAN - LESTARI, INTAN; DHARMAWAN, KOMANG; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 6 No 4 (2017)DO - 10.24843/MTK.2017.v06.i04.p175, 2017)
Agricultural insurance with the interantional price is new insurance in Indonesia. The international insurance premium is given if the international prices lower than the determined trigger value. The purpose of this study is to presents the steps needed to determine the premium value of the agricultural insurance. The steps are to search data of the international prices and local prices commodity coffee, calculate the return of both data, calculate descriptive statistic, calculate correlation between international prices of commodity coffee and local prices commodity coffee, estimate the parameter by using Maksimum Likelihood Estimasi(MLE), to do the Monte Carlo simulation by using Mean Reversion with Jump Diffusion, to determine the production cost, normality log test, to determine the trigger indexs, and to count the premium value with put cash-or-nothing option. On this study if international prices lower than the determined trigger value, trigger payments as much as Rp 20.248.282,4/Ha based on trigger index as many Rp 24.900/kg , so amount of premium payment equals Rp 334.000.